Acceptance Testing of Sate Lilit PAHU (Patin Fish and Tofu) Modification According to Infant and Child Feeding Principles as an Alternative to Prevent Stunting - Sherly Rahmawati; Taufiqurrahman; Mujayanto; Nuning Marina Pengge; Fahmi Hafid; Lee Shoo Thien (Journal of Nutrition Explorations, 2024)
Stunting for children under the age of 5 years is caused by long-term protein deficiency and it is a public health problem in Indonesia. Patin fish is rich in protein, selenium and taurine, which help stimulate the growth and development of children. The aim of study was to assess the acceptability of thigh skewers (made with Patin fish and tofu) as a potential alternative to prevent stunting in infants and children, based on the principles of proper nutrition. Experimental study was conducted on a control group and three treatment groups. Organoleptic test was conducted among 25 panelists by using indicators of color, taste, aroma and texture. The average distribution of formulas for SLT 0 (3.73), SLT 1 (3.91), SLT 2 (3.57), SLT 3 (2.85). The most preferred formula was SLT 1. The SLT 1 consisted of 70 grams of Patin fish and 30 grams of tofu. The protein content of one serving of Sate wrapped around the thigh (Patin fish and tofu) is adequate to meet the protein requirements of toddlers. It providing 7.55 g of protein per snack, with a protein energy ratio of 24.61% and energy density of 3.62.